Anthropogenic impact on Antarctic surface mass balance, currently masked by natural variability, to emerge by mid-century - Michael Previdi; Lorenzo M Polvani (Environmental Research Letters, 2016)
Global and regional climate models robustly simulate increases in Antarctic surface mass balance (SMB) during the twentieth and twenty-first centuries in response to anthropogenic global warming. Despite these robust model projections, however, observations indicate that there has been no significant change in Antarctic SMB in recent decades. We show that this apparent discrepancy between models and observations can be explained by the fact that the anthropogenic climate change signal during the second half of the twentieth century is small compared to the noise associated with natural climate variability. Using an ensemble of 35 global coupled climate models to separate signal and noise, we find that the forced SMB increase due to global warming in recent decades is unlikely to be detectable as a result of large natural SMB variability. However, our analysis reveals that the anthropogenic impact on Antarctic SMB is very likely to emerge from natural variability by the middle of the current century, thus mitigating future increases in global sea level.